ASUHAN KEPERAWATAN PRE EKLAMPSIA IBU HAMIL MELALUI TERAPI RENDAM KAKI AIR HANGAT DI RSHB BATAM - Chrisyelia Manuhutu; Dedi Fatrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Preeclampsia is a pregnancy-specific condition characterized by elevated blood pressure after 20 weeks of gestation in previously normotensive women, accompanied by edema and proteinuria. One non-pharmacological therapy that can help reduce blood pressure is warm foot soaking. This therapy produces a vasodilatory effect through the generation of thermal energy, improves blood circulation, and stimulates the parasympathetic nerves, leading to relaxation and decreased blood pressure. This study aimed to provide nursing care for Mrs. S, a pregnant woman with preeclampsia and discomfort, through the implementation of warm foot soak therapy at RSHB Batam City. The research employed a descriptive case study design conducted over four days, from February 17–20, 2025, using interviews and physical examinations based on the maternity nursing care format. Two main nursing diagnoses were identified: discomfort and risk of ineffective peripheral perfusion. The intervention included the application of warm foot soak therapy, followed by evaluations based on goals and outcome criteria. The results indicated improvements in comfort and blood pressure stability. This study is expected to serve as a reference for implementing nursing care in preeclampsia cases using complementary warm water therapy approaches.Keywords: Preeclampsia, Nursing Care, Pregnant Women, Warm Foot Soak.